2020
DOI: 10.5435/jaaos-d-19-00438
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Cannabis in Orthopaedic Practice

Abstract: Cannabis has gained widespread public advocacy since its legalization in several states with recent evidence suggesting that its self-reported use has increased in patients undergoing a primary total joint arthroplasty. The endocannabinoid system has been proposed to play a role in decreasing the inflammatory cascade and enhancing pain management. For these reasons, interest has emerged in the orthopaedic community as a potential treatment or adjunct to treatment in many musculoskeletal conditions. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In addition, a recent scoping review indicated that cannabis was effective in 67% of studies conducted within orthopaedic populations, 88 but that more high-quality evidence is needed. 89,90 However, a recent systematic review, showed very small improvement in pain, physical functioning, and sleep quality and no effect on emotional well-being when cannabis was used for the treatment of chronic pain. 33 Moreover, the opioid-sparing effects of medical cannabis remain unclear.…”
Section: Dovepressmentioning
confidence: 99%
“…In addition, a recent scoping review indicated that cannabis was effective in 67% of studies conducted within orthopaedic populations, 88 but that more high-quality evidence is needed. 89,90 However, a recent systematic review, showed very small improvement in pain, physical functioning, and sleep quality and no effect on emotional well-being when cannabis was used for the treatment of chronic pain. 33 Moreover, the opioid-sparing effects of medical cannabis remain unclear.…”
Section: Dovepressmentioning
confidence: 99%
“…3,4 Institutions such as the American Academy of Orthopaedic Surgeons have called for further research on cannabis. 5…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Institutions such as the American Academy of Orthopaedic Surgeons have called for further research on cannabis. 5 Several recent scientific investigations have focused on the adverse effects associated with marijuana use. 6 These reports primarily focus on the impact of marijuana on mental health, inflammation, and addiction.…”
Section: Introductionmentioning
confidence: 99%
“…The recent legalization of cannabis (recreational and/or medicinal) in many states has led to an increase in interest in its potential use for pain management after orthopedic procedures [ [4] , [5] , [6] , [7] , [8] , [9] ]. The self-reported use in patients undergoing TJA increased from 1% to 11% after its legalization in Colorado [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis may function to reduce sensitization of the nociceptive sensory pathways and induce alterations in cognitive and autonomic processing in selective chronic pain conditions [ 11 , 12 ]. However, the evidence to date does not support its use in patients undergoing orthopedic procedures [ [8] , [9] , [13] , [14] , [15] ]. Therefore, the primary purpose of this prospective study was to determine if cannabis use decreases narcotic consumption in patients undergoing TJA.…”
Section: Introductionmentioning
confidence: 99%